2016
DOI: 10.1016/j.jot.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinol stimulates bone formation and attenuates dexamethasone-induced inhibition of osteogenesis in larval zebrafish

Abstract: SummaryBackground/ObjectiveTanshinol is the main active component of Salvia miltiorrhiza Bunge, a significant Traditional Chinese Medicine used to treat cardiovascular disease. We have shown that tanshinol exerts an antiosteoporostic effect via the enhancement of bone formation in vivo and in vitro. However, the mechanism remains unclear. Based on the polyphenol group in the structure of tanshinol, we speculate the protective action on skeletal tissue is related to antioxidative capacity. Our in vitro evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 37 publications
(55 reference statements)
6
51
0
Order By: Relevance
“…Several studies have reported the use of alizarin red S to screen for molecules with osteogenic and mineralogenic bioactivities in zebrafish. They assessed the mineralization of cranial bones in larvae exposed from 3 to 9 dpf (Luo et al, 2016), or the count of vertebral bodies at 10 dpf (Yu et al, 2008), but none considered inter-specimen variability or accurately quantified the osteogenic effect. They also failed to provide a medium/high-throughput approach, utilised long exposures, late endpoints and a laborious image acquisition procedure, and therefore have limited applicability for large-scale screening of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the use of alizarin red S to screen for molecules with osteogenic and mineralogenic bioactivities in zebrafish. They assessed the mineralization of cranial bones in larvae exposed from 3 to 9 dpf (Luo et al, 2016), or the count of vertebral bodies at 10 dpf (Yu et al, 2008), but none considered inter-specimen variability or accurately quantified the osteogenic effect. They also failed to provide a medium/high-throughput approach, utilised long exposures, late endpoints and a laborious image acquisition procedure, and therefore have limited applicability for large-scale screening of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish is an ideal animal model in vivo for studying bone deformations for the high similarity of the structure and genetics of bone with human beings. 34,44 The bone of zebrafish larval contains the sufficient and necessary cells for both bone formation and resorption activity. 33 In the present study, we examined the bone mineralization by calcein staining, which is a vital dye staining and the biological mineralization process of zebrafish at phenotypic can be observed directly.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX)-induced osteopenia zebrafish larvae has been proved to be a well-established animal model for study of osteoporosis. 34 In this study, zebrafish larvae at 96 hpf (hours post fertilization) were exposed to DEX solutions with a concentration of 25 μM/L (DEX+), and 0.01% DMSO (DEX-) was selected as the vehicle control. Etidronate disodium (ED) is known to reduce bone resorption through the inhibition of osteoclastic activity.…”
Section: Ba Enhances Growth and Development Of Dexamethasone (Dex)-inmentioning
confidence: 99%
“…WT can be treated as a fast-evolving mathematical and signal processing tool in dealing with nonstationary signals [66] and has been widely applied in many engineering fields for decomposing, denoising, and signal analysis over nonstationary signals [26,42]. Continuous wavelet transform (CWT) and discrete wavelet transform (DWT) are two categories of WT.…”
Section: Maximal Overlap Discrete Wavelet Packet Transform (Modwpt)mentioning
confidence: 99%
“…EMD has some problems such as over envelope, end effects, and mode mixing [22][23][24]. The effectiveness of STFT is still hampered by the limitation of single triangular basis [25,26]. WVD can produce interference terms on the time-frequency domain in a critical condition and high computational complexity [27].…”
Section: Introductionmentioning
confidence: 99%